2010
DOI: 10.1038/modpathol.2010.43
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of protein kinase C β II expression in R-CHOP-treated diffuse large B-cell lymphoma patients

Abstract: Development of targeted agents for the treatment of diffuse large B-cell lymphoma includes clinical evaluation of enzastaurin, an agent that suppresses signaling through protein kinase C-b and AKT pathways. To determine whether protein kinase C-b expression has prognostic significance for diffuse large B-cell lymphoma patients treated with immunochemotherapy, we analyzed the expression of protein kinase C-b II, BCL-2 and cell of origin immunohistochemically from pretreatment samples of 95 diffuse large B-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…A previous study has also reported that increase in PKC correlates to positive Her2/neu receptor status, negative estrogen and progesterone receptor status, and poor survival [505]; however, this finding has recently been challenged by another study suggesting that there is no correlation between PKC expression and clinicopathological parameters (tumor grade and estrogen/progesterone receptor negativity) and recurrence-free or 10-year survival [60]. In DLBCL, PKC II expression is significantly associated with low response to chemotherapy and poor survival in patients [354][355][356][357]. Furthermore, PKC can be used as a prognostic indicator in NSCLC and ovarian cancer [306,500].…”
Section: Pkc Isozymes As Diagnostic or Prognostic Biomarkersmentioning
confidence: 74%
See 2 more Smart Citations
“…A previous study has also reported that increase in PKC correlates to positive Her2/neu receptor status, negative estrogen and progesterone receptor status, and poor survival [505]; however, this finding has recently been challenged by another study suggesting that there is no correlation between PKC expression and clinicopathological parameters (tumor grade and estrogen/progesterone receptor negativity) and recurrence-free or 10-year survival [60]. In DLBCL, PKC II expression is significantly associated with low response to chemotherapy and poor survival in patients [354][355][356][357]. Furthermore, PKC can be used as a prognostic indicator in NSCLC and ovarian cancer [306,500].…”
Section: Pkc Isozymes As Diagnostic or Prognostic Biomarkersmentioning
confidence: 74%
“…Several PKC isozymes (PKC , I, II, , , , and ) are detected in CLL, but PKC II shows the highest expression [351][352][353] and plays a more important role in cell proliferation, differentiation, survival, and anticancer drug resistance. Overexpression of PKC II in CLL is also associated with poor prognosis and patient survival [354][355][356][357]. For these reasons, PKC II is considered a useful therapeutic target for the treatment of CLL; however, inhibition of a PKC II activity with PKC II-specific inhibitor (e.g., LY379196) has a minimal effect on the viability of CLL cells [351,358].…”
Section: Myeloid and Lymphocytic Leukemiamentioning
confidence: 99%
See 1 more Smart Citation
“…PKCb is overexpressed in 20-25% of DLBCL at diagnosis and 90% at relapse (37,38). Hyperexpression of PKCb has been associated with resistance to immunotherapy (39) and poor prognosis in DLBCL (38). These observations make PKCb a putative drug target.…”
Section: Discussionmentioning
confidence: 96%
“…Overexpression of PKC␤ is implicated in the pathogenesis of B-cell lymphoma and has prognostic significance in diffuse large B-cell lymphoma. 48 Enzastaurin, an oral serine/ threonine kinase inhibitor, targets the PKC␤ as well as the PI3K/AKT pathways to inhibit tumor cell proliferation, induce apoptosis, and suppress tumor-induced angiogenesis.…”
Section: Pkc Inhibitionmentioning
confidence: 99%